An overview of key concepts in environmental knowledge: From ecology to sustainable development - Humaida, Nida; Murniningsih (UrbanGreen Central Media, 2022)
As human activities degrade the environment, comprehensive environmental knowledge is vital for sustainability. This paper reviews literature across disciplines to synthesize ecological principles, ethics, environmental threats, and solutions. Major challenges analyzed include climate change, biodiversity declines, pollution, and overexploitation. Conservation approaches like protected areas are examined, along with environmental law and sustainable development integrating economic, social, and ecological dimensions. Implementing sustainability requires transforming awareness, values, and behaviors toward environmental responsibility across society. Findings integrate insights from ecological and social sciences. This interdisciplinary framework informs urgent ethical policies and lifestyle changes to mitigate threats and uphold ecosystem integrity. Despite complex systemic challenges, creative collaboration can integrate human civilization and nature conservation for thriving societies.